(untitled) (International Journal of Islamic Business, 2017)
The issue of impulse buying behavior has been studied in numerous marketing fields particularly in buying behavior. Impulse buying behavior has been considered as one type of buying behavior frequently exercised among consumers in this modern age. There is a growing stream of research on impulse buying behavior, particularly from the retail purchasing context which revealed factors that contribute to this behavior. Generally, previous studies on impulse buying focused on three perspectives, namely individual factors (e.g. lack of self-control), product factors (e.g. low and high price), and situational factors (e.g. store environment). However, there are scarce conceptual and theoretical knowledge in marketing studies which discusses the influence of ‘cool’ motivation and credit card on impulse buying behavior. Therefore, the purpose of this conceptual paper is to review the relationship between ‘cool’ motivation and credit card on impulse buying behavior which in turn is expected to reveal a new perspective on the study of consumer behavior. It is essential to explore the relationship between ‘cool’ motivation (CM), credit card (CC) and impulse buying behavior (IBB) as less attention has been paid to this matter. Therefore, the results of this study will contribute to the current body of knowledge and provide additional valuable information to marketing practitioners which then will allow them to create effective and efficient marketing strategies.